AN EMPIRICAL STUDY ON ACCOUNT RECEIVABLES & ACCOUNT PAYABLES MANAGEMENT AT COMPOSITE INVESTMENTS PVT LTD, BANGALORE (Journal of Pharmaceutical Negative Results, 2022)
Working capital plays an important role in determining the financial strengths and weakness of a company. The project is entitled to “An Empirical Study on Account Receivables & Account Payables management at Composite Investments Pvt Ltd, Bangalore”. The main objective of the study is to analyse financial performance of the Composite Investments Pvt Ltd. Judgement sampling is considered and the sample size of the report is 5 financial years. Data collected is secondary data (balance sheet and profit and loss account) and analyzed using SPSS, by ratio analysis, trend analysis to understand the financial position of the company. It is found that there is a decrease in current liabilities and increase in the current assets over the considered financial years. The suggestions reveal that the company has to strongly focus on reducing working capital strategies that will make the company more profitable. The company has a bright future and can achieve the overall objectives of the company if it concentrates more on its working capital and short-term investments.